Impact of the sense of power on loneliness among international students in China: the chain mediating role of perceived discrimination and loneliness stigma - Qunming Yuan; Xinchang Lu; Xiaoli Shi; Jiaqi Leng; Zhiguang Fan (BMC Psychology)
Abstract Background Loneliness is a common emotional experience among international students that can affect their mental health, cultural adaptation, and academic development. Therefore, the present study aimed to explore the relationship between a sense of power and loneliness among international students, and to examine the mediating role of loneliness stigma and perceived discrimination. Methods The study used the generalized sense of power scale, experiences with discrimination scale, stigma loneliness scale (SLS), and UCLA loneliness scale-6 (ULS -6) for 529 international students in China. The study conducted descriptive statistical analysis, Pearson correlation analysis, Spearman correlation analysis, and chain mediation model test on the obtained data using SPSS 20.0 and PROCESS v4.0. Results The sense of power was significantly negatively related to perceived discrimination, and loneliness stigma, with the result that loneliness, and perceived discrimination, loneliness stigma, and loneliness were significantly positively related. The sense of power can directly affect international students’ loneliness (β = -0.167, t = -4.298, p < 0.01), or indirectly affect loneliness through three paths: the mediating role of perceived discrimination, the mediating role of loneliness stigma, and the chain mediating role of perceived discrimination and loneliness stigma. The total indirect effect value was -0.234, and the indirect effect values for each pathway were -0.153, -0.059, and -0.022, respectively. Conclusion A sense of power can directly affect loneliness in international students and indirectly by reducing perceived discrimination and loneliness stigma. The results of this study contributed to a better understanding of the relationship between a sense of power and loneliness and its mechanism, providing a reference for carrying on mental health education work for international students.